2018
DOI: 10.1053/j.ajkd.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Undocumented Immigrants With Kidney Disease

Abstract: The care of dialysis-dependent undocumented immigrants exemplifies a problem at the crux of 2 US national agendas: immigration and health care reform. Undocumented immigrants represent 3% of the US population and 27% of the uninsured, and an estimated 6,500 individuals are dialysis dependent. With no uniform national policy, an estimated 30% to 50% of these individuals receive treatment only in life-threatening situations (emergent dialysis). Since 2005, about 400 undocumented immigrants have received a kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 35 publications
1
42
0
5
Order By: Relevance
“…27 Few immigrants have been able to get coverage for regularly scheduled dialysis under unsubsidized commercial plans, but the sustainability of this option is unknown and still leaves many without coverage. 3 Although emergency dialysis is covered by law, 29 regularly scheduled dialysis is still not the standard of care for most undocumented immigrants in the United States. 30 Research has shown the potential benefits to both patients and the country of regularly scheduled dialysis, so continued advocacy for undocumented patients with ESRD is needed to make sure they get the proper care they deserve.…”
Section: Meeting Challenges Of Ckd In Undocumented Immigrantsmentioning
confidence: 99%
“…27 Few immigrants have been able to get coverage for regularly scheduled dialysis under unsubsidized commercial plans, but the sustainability of this option is unknown and still leaves many without coverage. 3 Although emergency dialysis is covered by law, 29 regularly scheduled dialysis is still not the standard of care for most undocumented immigrants in the United States. 30 Research has shown the potential benefits to both patients and the country of regularly scheduled dialysis, so continued advocacy for undocumented patients with ESRD is needed to make sure they get the proper care they deserve.…”
Section: Meeting Challenges Of Ckd In Undocumented Immigrantsmentioning
confidence: 99%
“…3 In the United States, current policy-the Omnibus Budget Reconciliation Act of 1985 and the Personal Responsibility and Work Opportunity Reconciliation Act (PWORA) of 1996excludes undocumented immigrants from federally financed public benefits including Medicare, Medicaid, the Children's Health Insurance Program, and Affordable Care Act (ACA) insurance subsidies and exchanges. [4][5][6][7][8][9] Enacted in 1986, the Omnibus Budget Reconciliation Act prohibited the use of federal funds for undocumented immigrants except in emergency situations, 8 as dictated by the simultaneous enactment of the Emergency Medical Treatment and Active Labor Act (EMTALA). Under EMTALA, all states must provide federally funded emergency medical treatment, including emergent-only hemodialysis, which would be needed for the care of failed kidney transplants.…”
Section: Commentarymentioning
confidence: 99%
“…Under EMTALA, all states must provide federally funded emergency medical treatment, including emergent-only hemodialysis, which would be needed for the care of failed kidney transplants. 4,6,10 In addition, 11 states and the District of Columbia currently use state funding sources to provide undocumented immigrants with maintenance dialysis. 11 Notably, kidney transplantation is not considered an emergency treatment for end-stage renal disease (ESRD) and thus, under this legislation, is not eligible to be federally subsidized for undocumented immigrants.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Undocumented immigrants comprise 3% of the U.S. population, with the majority residing in California, Florida, Illinois, New Jersey, New York and Texas . They also represent 27% of all people living in this country without the benefit of health insurance . Currently, in all 50 states, undocumented immigrants who have kidney failure must receive dialysis as an emergency treatment in emergency departments .…”
Section: States Of Mindmentioning
confidence: 99%